Optimalisasi Pengelolaan Data Nasabah Melalui Website BTN Smart di Bank BTN Kantor Cabang Pembantu UNESA Ketintang - Ajuj, Sausan Syarifatul; Fauziah, Sumaniah (Innovative: Journal Of Social Science Research, 2025)
This research focuses on optimizing customer data management through the BTN Smart website at Bank BTN UNESA Ketintang sub-branch office, as part of the digital transformation in banking services. The BTN Smart website is designed to increase the efficiency, effectiveness and security of managing customer data, as well as providing easy access to banking services for customers. This research aims to analyze the efficiency of using the BTN Smart website in managing customer data, evaluate the implementation of its features, and understand the role of digitalization in improving the quality of banking services. The use of the BTN Smart website in managing customer data at Bank BTN UNESA Ketintang Sub-Branch Office increases the efficiency and accuracy of the data input process, facilitates prospect management, and supports the implementation of digitalization through automation and effective real-time monitoring by staff and management.